Redox-responsive micellar drug delivery systems - Amer, Aseel (2026)
This paper reviews redox-responsive drug delivery systems (DDSs) that use micelles as the nanoparticle, focusing on the systems that utilize disulfide bonds, for applications in cancer treatment. Micelles exhibit high solubility for hydrophobic drugs with slow and sustained drug release. The encapsulation of drugs within the micelle increases its stability. Using redox as an intrinsic trigger is possible due to the higher concentration of GSH found in cancerous cells. Several papers utilizing in vivo and in vitro studies are discussed and summarized. A redox-responsive DDS targets tumor tissues by breaking the disulfide bond when exposed to a high GSH concentration, thereby minimizing cellular side effects and drug loss. The application of redox-responsive DDSs to overcome multidrug resistance (MDR) is examined in this paper. Multistimuli DDSs are shown to have the best outcome for treating MDR.